Sosialisasi Teknik Penyambungan Papan Kulit ke Gading dan Lunas pada Kapal Kayu dengan Rangka Konstruksi Baja - Sitepu, Ganding; Ardianti, Andi; Firmansyah, Muhammad Rizal; ., Misliah; Djafar, Wihdat; Djalante, A. H.; Bochary, Lukman; Clauthaldi, F. R.; Matemmu, Jeferi (Faculty of Engineering UNHAS, 2024)
The construction of wooden boats for fishermen in South Sulawesi is starting to find it difficult to get high-quality wood, especially for boat hulls. An alternative to wood as a wooden ship hull is steel. The problem of joining or fastening planking boards made of wood with a steel frame is not fully understood by the wooden boat craftsmen in Galesong. For this reason, this activity aims to socialize the binding of planking boards with wooden ship steel frames to the